Intraductal papilloma of the breast: A case report - Tarallo, V. (Elsevier, 2012)
Intraductal papillomatous lesions in the breast may be manifestations of different histological types of tumors, including papillomas and intraductal papillary carcinomas. Intraductal papillomas are relatively rare, with an incidence of 2–3%. They are benign tumors that arise from the mammary duct epithelium. We observed a tumor of this type in a 51-year-old woman who had noted bloody discharge from her right nipple. She was referred for breast sonography a few days later. The sonographic examination revealed a dilated duct enclosing a mass, which was surgically removed. Histological examination revealed that the lesion was benign (intraductal papilloma). This case illustrates the role of imaging in confirming clinical diagnoses of papillomatous lesions. Histological confirmation is always necessary, however, to rule out the presence of intraductal papillary carcinoma.